ANALISA PENGARUH PRODUCT, PRICE, PLACE, DAN PROMOTION TERHADAP KEPUTUSAN PEMBELIAN DI RUMAH MAKAN AYAM GORENG ECHO: The Effect of Product, Price, Place, and Promotion on Purchas Decision at ‘Ayam Goreng’ Echo Restaurant. - putri, nadia benita (PERFORMA, 2022)
This research is done to find out the effect of product, price, place, and promotion on purchasing decisions at ‘Ayam Goreng’ Echo restaurant. This research is quantitative research. This research sample is taken by using a non-probability sampling technique. The type of non-probability sampling that is selected is purposive sampling. Analysis method that is used is multiple linear regression analysis. Data source in this research is primary data that is obtained by distributing 140 questionnaires to customers of ‘Ayam Goreng’ Echo restaurant who have done purchase at least once in the last three months. The results of data analysis show that product, price, and promotion partially affect significant on purchase decision at ‘Ayam Goreng’ Echo restaurant, while place does not affect significant. The result of determination coefficient shows that product, price, place, and promotion can influence 85.7% of purchase decision. The result of this research provides practical implication for the management of ‘Ayam Goreng’ Echo restaurant regarding the importance of 4P marketing mix so that marketing strategy that is related to product, price, place, and promotion can improve customer purchase decision. Key words: Product, Price, Place, Promotion, Purchase Decision